Russian Prepositions with the Meaning of Proximity and Ways of Their Expression in the Persian Language - S. M. Aliyari; M. Ahmadi; H. Ghayedi (Научный диалог, 2017)
Russian common spatial prepositions with the meaning of proximity and ways of their expression in the Persian language are considered. It is noted that the Russian language has more than 33 prepositions with the meaning of proximity. The practical significance of the study is determined by the fact that understanding of their meanings is difficult for Iranian students, in particular, when choosing the appropriate equivalent in Persian. The authors of this study expect to establish and describe the existing relations between the common spatial prepositions with the meaning of proximity in the Russian language and their equivalents in the Persian language. The novelty of the research is seen in the fact that the relations between the various prepositions with the meaning of proximity in the comparative aspect are considered on the Russian-Persian material for the first time. 190 contexts in which spatial prepositions are used were analyzed. Material is extracted from a variety of sources, including artistic works, which were translated from Russian into Persian, explanatory and translation dictionaries as well as the National corpus of the Russian language.